2011
DOI: 10.1002/jpln.200800309
|View full text |Cite
|
Sign up to set email alerts
|

Use of reactive phosphate rocks as fertilizer on acid upland soils in Indonesia: accumulation of cadmium and zinc in soils and shoots of maize plants

Abstract: A pot experiment was conducted to study the contribution of reactive phosphate rocks (RPRs) on the accumulation of Cd and Zn in 10 acid upland soils in Indonesia and shoots of Zea mays plants grown on these soils. Two types of RPR were used at a rate of 0.5 g (kg soil)–1: RPRL containing 4 mg Cd kg–1 and 224 mg Zn kg–1, and RPRH containing 69 mg Cd kg–1 and 745 mg Zn kg–1. Zea mays was harvested at 6 weeks after planting. The application of RPRH significantly increased the concentrations of Cd in the shoots. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…There are some reports that application of Cdcontaining natural reactive phosphate rock can significantly increase the concentrations of Cd in the shoots of Zea mays (Rochayati et al 2011). However, we found a high ability of phosphates in reducing Cd solubility.…”
Section: Phytoextraction Of the Elements By Indian Mustard Rapeseedmentioning
confidence: 97%
“…There are some reports that application of Cdcontaining natural reactive phosphate rock can significantly increase the concentrations of Cd in the shoots of Zea mays (Rochayati et al 2011). However, we found a high ability of phosphates in reducing Cd solubility.…”
Section: Phytoextraction Of the Elements By Indian Mustard Rapeseedmentioning
confidence: 97%
“…These metals are also present in natural phosphate rock used as the raw material for the manufacture of fertilizer P [14,41]. Pb and Cd are known to have no physiological activity/function, and applying certain phosphate fertilizers adds Cd and other potentially toxic elements to the soil, such as F, Hg, and Pb [42]. Phosphate fertilizers can significantly contribute to hazardous trace elements such as arsenic (As), Cd, and Pb in croplands.…”
Section: Sources and Causes Of Pb And CD Pollution In Agriculture 41 ...mentioning
confidence: 99%
“…It enters the plants through the roots and is then translocated through the shoots in ionic form into the vascular bundles via ascending sap and/or transporters (Dong et al, 2019). Abbas et al (2017); Nahar et al (2016) and Rochayati et al (2011) reported that accumulation of Cd in plant tissues evoked physico-chemical anomalies including necrosis and ion homeostasis, chlorosis, limited micro and macronutrients uptake, net photosynthetic activity and ultimate retardation of growth. Higher cadmium content may entreat excessive production of reactive oxygen species with concomitant destruction of biomembranes by oxidation of lipids and proteins and biomolecules, as well as severe effects on the antioxidant defense system (Nagajyoti et al, 2010;Gallego et al, 2012).…”
Section: Introductionmentioning
confidence: 99%